Response of Long-Term Water and Phosphorus of Wheat to Soil Microorganisms - Junjie Hu; Yanhao Lian; Hui Guo; Zongzhen Li; Haifang Pang; Mengjiao Zhang; Yongzhe Ren; Tongbao Lin; Zhiqiang Wang (Agriculture)
Phosphorus deficiency critically constrains crop growth. Soil microbial diversity, which is crucial for maintaining terrestrial ecosystem integrity, plays a key role in promoting soil P cycling. Therefore, it is imperative to understand the survival strategies of microorganisms under P-limited conditions and explore their roles in community regulation. We initiated a comprehensive, long-term, in situ wheat field experiment to measure soil physicochemical properties, focusing on the different forms of soil inorganic P. Subsequently, 16S rRNA and ITS marker sequencing was employed to study changes in soil microbial abundance and community structure and predict functional alterations. The results showed that soil water and P deficiencies significantly affected wheat growth and development, soil physicochemical properties, and microbial diversity and function. Prolonged P deficiency lowered soil pH, significantly increasing phosphatase content (58%) under W1 (normal irrigation) conditions. Divalent calcium phosphate decreased significantly under W0 (lack of irrigation) and W1 conditions, and the most stable ten-valent calcium phosphate began to transform under W0 conditions. Soil microbial diversity increased (e.g., Proteobacteria and Vicinamibacterales) and enhanced the transport capacity of bacteria. P deficiency affected the coexistence networks between bacteria and fungi, and SEM (structural equation modeling) analysis revealed a stronger correlation in bacteria (r2 = 0.234) than in fungi (r2 = 0.172). In soils deprived of P for 7 years, the soil P content and forms were coupled with microbial changes. Microorganisms exhibited community and functional changes in response to low-phosphorus soil, concurrently influencing soil P status. This study enhances our understanding of rhizospheric processes in soil P cycling under microbial feedback, particularly the impact of microbial interactions on changes in soil P forms under P-limited conditions.